The comparison of the conventional development and sustainable development model - Labović Bojan (University Business Academy - Faculty of Economics and Engineering Management, Novi Sad, Serbia, 2021)
Great ideas usually start out as rather simple ideas. In social sciences, the ideas which impact the lives of the millions and which direct policies must be available to all, not only to the elite. Only in this way can they properly permeate institutions from the global to the local level and become an integral part of human lives. The model of sustainable development challenges the conventional model of development. Namely, the conventional approaches simplify development by observing it as global modernization modeled after the example of industrialized, developed countries. Sustainability does not simply require balancing, i.e. compromising between inherently conflicting forces. It is rather a positive imperative which connects social, economic, and ecological benefits. Sustainable development advocates for the ethical position that the stock of natural resources must be preserved for the future generations and that the value of all social benefits and costs, including the depletion of natural resources, must be included in accounting systems for the development performances to be properly measured. This paper covers a wide gap between the theoretical interpretation of sustainable development and the current situation in the world. The paper presents some critical views which perceive sustainable development as an illusion, but also gives arguments which claim that sustainable development has no alternative.